PARASITIC CONTAMINATION OF VEGETABLES SOLD AT HAYIN DANMANI MARKET IN KADUNA METROPOLIS, KADUNA STATE, NIGERIA. - Dikwa, Karderam Bukar; Sahabi, Regina; Emmanuel, Olinya Chibuike; Uchenna, Nwigwe; Bakare, Oluwadamilola; Aminu, Solomon Ghaddafi (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Vegetables commonly sold at Hayin Danmani market in Kaduna Metropolis were screened for possible contamination by intestinal parasites. A total of 106 samples of nine different varieties of vegetables were purchased and examined via sedimentation centrifugation method between January to May 2016. Overall results shows 66 (62.3%) vegetables were contaminated with various stages of intestinal parasites. The prevalence of parasitic contamination recorded were: Lettuce (Lactuca sativa) 12(85.7%), Cabbage (Brassica oleracae) 12(85.7%), Tomatoes (Lycopersicum esculentum) 4 (33.3%) , Green Onion (Allium cepa% ) 6(50.0), Cucumber (Cucumus sativa) 8(6.7%), Roselle leaves (Hibiscus sabdariffa) 7(58.3%), Carrot (Daucus carota) 6 (60.0%), Spinach (Spinacia oleracae) 7(70.0%) and Jute leaves (Corchorus olitorius) 4(40.0%). Consumption of such vegetables without adequate washing may be a source of transmission of intestinal parasites and may play a major role in the epidemiology of intestinal parasites.